Association of baseline plasma fibrinogen levels with cognitive and affective status at 30 and 90 days in individuals with ischemic stroke: A prospective study from Nigeria - Adekola B. Ademoyegun; Taofeek O. Awotidebe; Marufat O. Odetunde; Samuel O. Inaolaji; Serifat O. Bakare; Funmilola W. Azeez; Olanrewaju Olayemi (Brain Circulation)
BACKGROUND: The influence of fibrinogen as a risk factor in developing poststroke neuropsychological and cognitive problems is underreported. This study aimed to evaluate the relationship between baseline fibrinogen levels and depression, anxiety, and cognition 30- and 90-day after stroke. METHODS: This prospective study involved 48 patients with first-ever mild-to-moderate ischemic stroke, whose plasma fibrinogen levels were assessed within 24 h of stroke onset. Clinical depression, anxiety, and cognitive impairment were evaluated by the Hospital Anxiety and Depression Scale and Montreal Cognitive Assessment at 30- and 90-day after stroke. RESULTS: After adjusting for important covariates, the multiple linear regression models showed that baseline plasma fibrinogen was associated with the symptoms of depression, anxiety, and cognitive decline at both 30- and 90-day follow-up (P < 0.05). The receiver operating characteristic curve showed that baseline fibrinogen threshold > 409.0 mg/dl (82.4% sensitivity and 71.0% specificity), >405.0 mg/dl (80.0% sensitivity and 71.4% specificity), and > 400.0 mg/dl (80.6% sensitivity and 76.5% specificity) could respectively predict the presence of depression, anxiety, and cognitive impairment 90 days after stroke. CONCLUSIONS: High levels of baseline plasma fibrinogen are associated with the onset and severity of symptoms of depression, anxiety, and cognitive decline at 30 and 90 days after stroke. This study shows that fibrinogen may be a viable target for monitoring and intervention in the management of poststroke neuropsychological and cognitive disorders. Future clinical trials are needed to clarify whether defibrinogenation will prevent or reduce the rate and severity of symptoms of depression, anxiety, and cognitive decline among patients with ischemic stroke. TRIAL REGISTRATION: Pan African Clinical Trial Registry (registration number: PACTR202406755848901).